Paradigma Sosiologi Hukum Keluarga Islam di Indonesia (Rekonstruksi Paradigma Integratif Kritis) - Edi Rosman (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2013)
This paper intends to describe the reconstruction paradigm offers family law of Islam in Indonesia. Islamic Family Law is a representation of the overall Islamic law that has grown and developed based on the classic paradigm literalistik. Reliability paradigm literalistik often swayed by the paradigm of contemporary liberal. Conflict paradigmatic implications for disparity between empirical and normative law and Islamic family law actuality the loss itself. Abnormalities and the condition of the conflict that began with the anomaly requires a knowledge revolution. Revolution stimulated the birth of a new paradigm of knowledge, which is critical integrative paradigm. Paradigm is a critical integrative paradigm underlying social facts, social definitions and paradigms of social behavior with Islamic theological value.